THE RELATIONSHIP OF GRADING AND HISTOPATHOLOGY WITH RESULTS OF HER-2 PATIENTS' IMMUNOHISTOCHEMICAL EXAMINATION BREAST CANCER AT DR PIRNGADI MEDAN REGIONAL GENERAL HOSPITAL IN 2018-2019 - Mustika, Suryani Eka; Pangestuti, Dewi (Medicina Biomedica Journal, 2022)
Basic Health Research Data 2019 explains that breast cancer prevalence that occurs in Indonesia is the second malignancy phenomenon that often afflicts women with a percentage of 0.5%, and ranked first cervical cancer as much as 0.8%. To choose and predict the prognosis, immunohistochemical examination becomes part of the mandatory examination effort. The general purpose of this study is to test the relationship of grading histopathology and histopathology types with the results of the HER-2 immunohistochemical examination of breast cancer patients at Dr. Pirngadi Medan Hospital in 2018-2019. This type of research is observational analytics conducted using the Cross- Sectional method. Secondary research data in the form of breast cancer patients in the Anatomical Pathology section of Dr. Pirngadi Medan Hospital year 2018-2019. How to take a sample by total sampling method. The statistical test used in the study is the Chi-square test. The study found 66 cases. Breast cancer cases are most common in the age range between 40 to 49 years (43.9%). The most common stages are in stage III (53.0%). This type of histopathology is found in invasive ductal carcinoma (84.8%). The most histopathological grading was grade II (63.6%). HER-2 test results found that the majority of patients had HER-2 +3 (positive 3) (59.1%). As for the Chi-Square test, if p ≤ 0.05 found a significant association and if p ≥ 0.05 did not have a significant association. There is no significant association between the type of histopathology and the results of HER-2 immunohistochemical examination (p = 0.208) and there is no significant association between grading histopathology results of HER-2 immunohistochemical examination (p = 0.492).